ANALISIS HUKUM PEMBERHENTIAN TIDAK DENGAN HORMAT APARATUR SIPIL NEGARA DI KOTA PALOPO - Riyad Atmaja Herman; Abdul Razak; Anshori Ilyas (The Juris, 2023)
This study aims to analyze and identify how the position of the Joint Decree on Disrespectful Dismissal of State Civil Apparatus to dismiss people who have served their criminal sentences based on Court Decisions with Permanent Legal Force (inkracht van gewijsde). The type of research used is the type of empirical research. This research was conducted in the City of Palopo, Province of South Sulawesi, namely at the Office of the Office of the Human Resources and Human Resources Development Agency in the City of Palopo. The results obtained through library research and interviews were then analyzed using qualitative analysis methods with an empirical approach. The results of the study show that: 1) The Joint Decree between the Minister of Home Affairs, the Minister of State Apparatus Empowerment & Bureaucratic Reform and the Head of the State Civil Service Agency (Number 182/659/SJ, Number 15 of 2018, Number 153/Kep/2018) of 2018 does not mention specifically about the imposition of sanctions. 2) The central government should not only try to terminate civil servants/ASN convicted of corruption but also should hold accountability from civil servants/officials who have so far not dismissed civil servants convicted of corruption. So that it becomes a serious emphasis for PPK / PyB who deliberately do not carry out the orders of the Law and avoid abuse of authority in the form of the term selective logging in imposing sanctions on Corruption Civil Servants / ASNs. 3) Dishonorable Dismissal (PTDH) as referred to in the Joint Decree between the Minister of Home Affairs, the Minister of State Apparatus Empowerment & Bureaucratic Reform and the Head of the State Civil Service Agency (Number 182/659/SJ, Number 15 of 2018, Number 153/Kep/2018) The year 2018 should be a learning experience for all of us, especially for state administrators. Because of that, PPK / PÑƒB always conducts guidance and supervision of the State Civil Apparatus in Palopo City which must be continuously carried out and developed. Basically every human being does not want to be watched so there are always people who do as they please. That's why supervision plays a very important role to ensure that everyone carries out their duties properly. Discipline training also needs to be done to change the attitude of employees.